Historical Deconstruction of Śrī Mahārāja Śrī Jayāmrta in the Sukun Inscription of 1083 Śaka - Rakaihino Galeswangi (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: Śrī Mahārāja Śrī Jayāmṛta, who issued the Sukun inscription (1083 Śaka), is tentatively thought to be related to the Sukun Village, Sukun District, Malang City, based on the inscription obtained from a trader in Malang. The issue raised is deconstructing the history of the character Śrī Jayāmṛta and his relationship with a place called Sukun. The research method is a five-stage historical method: topic selection, source collection (heuristics), criticism, interpretation, and historical writing (historiography). The research results state that Śrī Jayāmṛta, who issued the Sukun inscription (1083 Śaka ), was not the king of the Kadiri Kingdom. He was a king of the Dharmmawangśā Tguh lineage whose original name was Sang Apanji Wijayāmṛtawarddhana. Śrī Jayāmṛta in the Sukun inscription is Śrī Jayawarsa Digwijaya Śāstraprabhu, who issued the Mruwak inscription and the Sirah Kĕtĕng inscription. Following the discovery of the Mruwak inscription and the Sirah Kĕtĕng inscription in the Madiun-Ponorogo area, the Sukun Village mentioned in the Sukun inscription must be searched for in the Madiun-Ponorogo area. In Ponorogo Regency, there are two areas called Sukun: Kampung Sukun, Kauman Village, Ponorogo District, and Sukun Hamlet, Sidoharjo Village, Pulung District. One of them is, of course, what is meant in the Sukun inscription. Abstrak: Śrī Mahārāja Śrī Jayāmṛta, yang mengeluarkan Prasasti Sukun (1083 Śaka), diduga sementara memiliki keterkaitan dengan wilayah Kelurahan Sukun, Kecamatan Sukun, Kota Malang, berdasarkan keberadaan prasasti yang diperoleh dari seorang pedagang di Malang. Permasalahan utama dalam penelitian ini adalah melakukan dekonstruksi terhadap sejarah tokoh Śrī Jayāmṛta dan hubungannya dengan tempat yang disebut Sukun. Metode penelitian yang digunakan adalah metode sejarah lima tahap, yaitu: pemilihan topik, pengumpulan sumber (heuristik), kritik sumber, interpretasi, dan penulisan sejarah (historiografi). Hasil penelitian menunjukkan bahwa Śrī Jayāmṛta yang mengeluarkan Prasasti Sukun (1083 Śaka) bukanlah raja dari Kerajaan Kadiri. Ia adalah raja dari garis keturunan Dharmmawangśā Tguh dengan nama asli Sang Apanji Wijayāmṛtawarddhana. Śrī Jayāmṛta yang disebutkan dalam Prasasti Sukun adalah tokoh yang sama dengan Śrī Jayawarsa Digwijaya Śāstraprabhu, yang juga mengeluarkan Prasasti Mruwak dan Prasasti Sirah Kĕtĕng. Berdasarkan penemuan Prasasti Mruwak dan Prasasti Sirah Kĕtĕng di wilayah Madiun-Ponorogo, maka lokasi Desa Sukun yang disebut dalam Prasasti Sukun kemungkinan besar berada di wilayah tersebut. Di Kabupaten Ponorogo, terdapat dua wilayah bernama Sukun, yakni Kampung Sukun di Kelurahan Kauman, Kecamatan Ponorogo, dan Dusun Sukun di Desa Sidoharjo, Kecamatan Pulung. Salah satu dari keduanya diyakini merupakan wilayah yang dimaksud dalam Prasasti Sukun.